1999
DOI: 10.1046/j.1365-2109.1999.00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Diel feeding rhythms of greenback flounderRhombosolea tapirina(Günther 1862): the role of light-dark cycles and food deprivation

Abstract: The role of light–dark (LD) cycles and food deprivation in the regulation of diel feeding rhythms in greenback flounder Rhombosolea tapirina (Günther 1862) was examined. A computerized monitoring system was developed to record uneaten pellets, and food intake was estimated as the difference between pellets presented and those uneaten. Three groups of five fish each (75–281 g) were exposed sequentially to the LD cycles: LD 12:12, LD 12:12 (scotophase advanced by 9 h), LD 6:18, DD, LD 6:6:6:6, LL and LD 12:12 (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“… sub-optimal. This agreed with field and laboratory observations that greenback flounder prefer to feed during light hours (Crawford, 1984;Chen et al, 1999). The regime of one 3 h meal during photophase (1M/L) resulted in equally good growth as under the other feeding regimes except 1M/D (Table I).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“… sub-optimal. This agreed with field and laboratory observations that greenback flounder prefer to feed during light hours (Crawford, 1984;Chen et al, 1999). The regime of one 3 h meal during photophase (1M/L) resulted in equally good growth as under the other feeding regimes except 1M/D (Table I).…”
Section: Discussionsupporting
confidence: 89%
“…data). A recent study (Chen et al, 1999) has revealed that the fish prefer to feed during the photophase, but a bout of feeding activity occurs also during the scotophase particularly after a period of food deprivation.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in diel activity of fishes are a common response to differences in biotic and abiotic environmental factors, including predator abundance, prey availability, presence/absence of competitors, habitat structure, depth, and abiotic conditions such as temperature and light levels (Chen et al 1999, Reebs 2002, Hansen et al 2004, Andrews et al 2009, Côté & Maljković 2010. Because these factors may vary regionally, and because invasion is often accompanied by release from the natural controls of competition and predation (Mack et al 2000), behavioral differences in invasive species are therefore likely between native and invaded locations.…”
Section: Introductionmentioning
confidence: 99%
“…Ad libitum feeding is often affected by light: some fish are nocturnal feeders (European sea bass: Boujard et al 1996) and some are diurnal (greenback flounder: Chen et al 1999;spotted wolffish: Foss et al 2003). OC and AE inevitably follow the natural feeding pattern; however, if feed is provided at specific times unrelated to the circadian rhythm, fish can often adjust to the imposed schedule (walleye: Yager and Summerfelt 1994; European sea bass: Boujard et al 1996;Azzaydi et al 1998;tench: Zakes et al 2006).…”
Section: Subscripts (Compartments)mentioning
confidence: 99%